The status of the Ring Ouzel Turdus torquatus in the UK in 2012. Issue 2 (2nd April 2016) - Wotton, Simon R.; Stanbury, Andrew J.; Douse, Andrew; Eaton, Mark A.
ABSTRACT: Capsule: There were up to 6348 Ring Ouzel territories in the UK in 2012. Aims: To produce estimates of the size of the Ring Ouzel breeding population in the UK and its constituent countries. Methods: A stratified random selection of tetrads was surveyed within the known breeding range, except for the remaining breeding areas on Dartmoor and historical sites elsewhere, which were surveyed in their entirety. The methods followed those devised for the first UK-wide survey in 1999, using playback of song at specific points along tetrad transect lines. Results: The UK population estimate in 2012 was 5332 (95% confidence limits (CL), 4096–6875) territories, a non-significant decline of 29% since 1999. There were no significant differences in the population changes in England, Scotland and Wales between the two surveys. An estimation of survey efficiency found that 84% of territories were located by the national survey methods, suggesting that the UK population in 2012 could have been as many as 6348 (95% CL, 4825–8198) territories. Conclusion: The results suggest that the UK Ring Ouzel population has continued to decline since 1999. Ongoing and future research should determine where the main threats to the population are: on the breeding or wintering grounds, or during migration.